(untitled) (The Journal of Medicine, Humanity and Media, 2026)
This issue of the Journal of Medicine, Humanity and Media (Vol. 3, No. 4) brings together selected papers from the 8th International Conference on “Medicine, Humanity and Media” (MHM 2025) & Doctoral Symposium, along with regular submissions addressing emerging topics in digital health communication, artificial intelligence, and cultural perspectives on well-being. Centered on the theme “Health Communication and Cultural Construction in the Age of Intelligence,” this collection reflects the field’s deepening engagement with technology, culture, and global health contexts, while highlighting the integration of humanistic reflection with computational innovation.